Evaluation of Participants’ Opinions on Online Physical Fitness Training - Ayla Bicen; Hüseyin Uzunboylu; Nazim S. Burgul (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The purpose of this study was to evaluate the opinions of online participants on physical fitness training during the years of 2017-2018. In this regard, the opinions of 347 online participants were obtained through structured questionnaires. The responses of participants were reviewed and analyzed with the help of smart-PLS. The duration of this training was 8 weeks and participants were asked about changes that occurred in their mind and body during the entire training process and what opinion they formed about the training program. The findings reveal that the training education expectations of participants were exceedingly met in general and that it enhanced their motivation and physical strength levels to a great extent. All the participants admitted that training education was successful and that it made a positive impact on their opinions.